(3HQfGeL ebJQM bGie Ydi GdfXQjI GdHfGijI dJfejI eaGgje hegGQGJ JUeje GdehGbY GdGdcJQhfjI GdJYdjejI dWdGH cdjI GdJQHjI hCKQg aj GJLGgGJge fMh GdeGOI (B/s - (3NGdO CMeO YHO GdMejO jhfS (B/s; (3eMeO(B,(3eUWai YHO GdSejYs; (3EHQGgje(B,(3HgjQI Tajbs; (3LGeYI GdbGgQIs (3cdjI GdOQGSGJ GdYdjG ddJQHjI ,s (3bSe GdefGgL h WQb GdJOQjS(B.s ([(3GdLjRI(B]:s [(3LGeYI GdbGgQI(B](3,s, 2015)
b
(3cdjI GdJQHjIs
(3HMK ebOe dfjd OQLI OcJhQGI ai GdadSaI ai GdJQHjI (B"(3JNUUGdefGgL h WQb GdJOQjS HcdjIGdJQHjI (B- (3LGeYI (B6 (3GcJhHQs
(3jTJed Ydi EQLGYGJ HHdjhLQGajI (B.s
(3eJGM fSNI Ydi bQU VhFi(B.s
(3jMJhi Ydi edNU HGddZI GdGfLdjRjI U (B:a:k.s
Keywords: (3WQb GdJOQjSs -- (3GdadSaIs; (3GdefGgLs; (3GdehGbY GdGdcJQhfjIs